Beginning Microsoft Visual C 2010 - Watson, Karli; Nagel, Christian; Pedersen, Jacob Hammer; Reid, Jon D; Skinner, Morgan (Wrox programmer to programmer, 2010)
Update to Wrox's leading C# book for beginners Get ready for the next release of Microsoft's C# programming language with this essential Wrox beginner's guide. Beginning Microsoft Visual C# 2010 starts with the basics and brings you thoroughly up to speed. You'll first cover the fundamentals such as variables, flow control, and object-oriented programming and gradually build your skills for Web and Windows programming, Windows forms, and data access. Step-by-step directions walk you through processes and invite you to "Try it Out," at every stage. By the end, you'll be able to write useful programming code following the steps you've learned in this thorough, practical book. The C# 4 programming language version will be synonymous with writing code with in C# 2010 in Visual Studio 2010, and you can use it to write Windows applications, Web apps with ASP.NET, and Windows Mobile and Embedded CE apps Provides step-by-step instructions for mastering topics such as variables, flow controls, and object-oriented programming before moving to Web and Windows programming and data access Addresses expressions, functions, debugging, error handling, classes, collections, comparisons, conversions, and more If you've always wanted to master Visual C# programming, this book is the perfect one-stop resource. Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.